Limited impact of roselle flower extract on protein carbonyl levels after physical exercise in healthy men - Ayubi, N.; Rusdiawan, A.; Hartoto, S.; Wibawa, J.C.; Rizki, A.Z.; Afandi, A.; Wardani, A.P.S.; Halip, M.F.; Jr, P.B.D. (Medicni Perspektivi, 2025)
Exercise-induced oxidative stress can lead to muscle damage, with protein carbonyls serving as a key biomarker of oxidative modification in proteins. Roselle flower extract contains polyphenols with potential antioxidant properties that may reduce oxidative damage after physical exercise. This study investigated whether post-exercise supplementation of roselle flower extract reduces protein carbonyl levels. A randomized controlled trial with a parallel group pre-test/post-test design was conducted, comparing a placebo group with a treatment group receiving 500 mg of roselle flower extract. The extract did not result in a statistically significant reduction in protein carbonyl levels (p>0.05). However, a non-significant decreasing trend was observed, suggesting that future studies should explore larger sample sizes and longer intervention periods to assess potential cumulative effects. Further studies should explore the effects of higher doses of roselle flower extract (e.g., >500 mg/day) and chronic supplementation over several weeks to determine its long-term impact on markers of oxidative stress.